Demokrasi Dalam Pendidikan Islam - Kasful Anwar; Sya’roni Sya’roni; Anggun Feronika; Si’in Si’in (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This paper will discuss democracy in Islamic education. The discussion on democracy in Islamic education starts from the most general definition of democracy, then democracy aims to provide equal opportunities for every student to achieve the highest level of education according to his abilities. As for what is meant by democracy is defined as an ideology or a way of life that prioritizes equal rights, obligations, and treatment for all citizens. In the context of education, democracy is shown by giving equal attention and effort to students, regardless of their natural ability, health or social status.